2022
DOI: 10.3389/fimmu.2022.1066361
|View full text |Cite
|
Sign up to set email alerts
|

Myomedin replicas of gp120 V3 loop glycan epitopes recognized by PGT121 and PGT126 antibodies as non-cognate antigens for stimulation of HIV-1 broadly neutralizing antibodies

Abstract: IntroductionImprinting broadly neutralizing antibody (bNAb) paratopes by shape complementary protein mimotopes represents a potential alternative for developing vaccine immunogens. This approach, designated as a Non-Cognate Ligand Strategy (NCLS), has recently been used for the identification of protein variants mimicking CD4 binding region epitope or membrane proximal external region (MPER) epitope of HIV-1 envelope (Env) glycoprotein. However, the potential of small binding proteins to mimic viral glycan-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…In our previous work, we demonstrated that the human myomesin-1 domain 10 structure exhibited sufficient stability to be used as a scaffold for the generation of a highly complex combinatorial library using randomization of 12 mutable amino acid residues located in the three-domain loops, named Myomedin scaffold [ 34 , 39 ]. Based on the available crystal structure of mouse/human PD-1/PD-L1 complex (PDB ID 3bik), it seems to be evident that critical interaction residues of human PD-L1 required for the recognition of PD-1 receptor are located on β-sheet surface (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, we demonstrated that the human myomesin-1 domain 10 structure exhibited sufficient stability to be used as a scaffold for the generation of a highly complex combinatorial library using randomization of 12 mutable amino acid residues located in the three-domain loops, named Myomedin scaffold [ 34 , 39 ]. Based on the available crystal structure of mouse/human PD-1/PD-L1 complex (PDB ID 3bik), it seems to be evident that critical interaction residues of human PD-L1 required for the recognition of PD-1 receptor are located on β-sheet surface (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The injected substances were well tolerated for several days after application as the mice used for the imaging study were sacrificed approximately 2 weeks after the imaging without clinical and neurological marks of alterations. In support, we have previously published experiments on Myomedin-derived binders (each containing 10 µg) for immunization (in Freund adjuvant) through intradermal application of experimental BALB/c mice [ 34 , 39 ]. We did not record any marks of somatic or behavioral alterations, with exception of local irritation due to adjuvant co-administered with individual Myomedins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation